Global response of Vibrio cholerae to predation by heterotrophic protists - Hu, Jie (2015)
Vibrio cholerae, a Gram-negative bacterium that causes cholera, has played a significant role in the path of human history. Previous studies show protozoan predation is the main biological factor constraining bacterial growth in the environment. In response to predation, bacteria have evolved complex strategies to escape predation, and many of these may lead to a pathogenic lifestyle. A better understanding of the interactions between V. cholerae and protozoa is not only important from an ecological perspective, but also important from a human health perspective. The objectives of this study are to: (1) study the transcriptomic and proteomic response of V. cholerae A1552 biofilms to grazing by Acanthamoeba castellanii and Tetrahymena pyriformis; and (2) identify the chemical cues produced by T. pyriformis which induce grazing resistance of V. cholerae A1552. Transcriptomic analysis revealed that 291 transcripts were differentially regulated between biofilms grazed by A. castellanii and ungrazed biofilms. Among them, 93 transcripts were up-regulated and 198 were down-regulated. Transcripts differentially expressed included biosynthetic and metabolic genes, flagellar and chemotaxis genes, genes encoding cell wall and outer membrane proteins, and transcriptional and translational regulators. Proteomic analysis revealed that 20 proteins were differentially expressed in biofilms grazed by protozoa compared to ungrazed biofilms. Interestingly, only 10% of the proteins and transcripts detected as differentially expressed were found in both data sets. The metabolism of tyrosine was down-regulated in both transcriptomic and proteomic data in grazed samples compared to un-grazed samples, which indicates that the tyrosine metabolic regulon (VC1344-1347) may have an important role in the response of V. cholerae biofilms to A. castellanii predation. Indeed, a pigmented mutant, disrupted in VC1345 (hmgA), survived 100-fold better intracellularly in amoebae than did the wild type. The biomass of V. cholerae biofilms increased when the cell-free supernatant from a T. pyriformis culture was added, indicating that there may be chemical cues involved. Addition of inorganic nutrients at levels which are found in the grazer cell-free supernatants to the V. cholerae cultures did not completely compensate for this increase in biofilm biomass. However, the addition of nutrients did result in a similar increase in biomass when the pH of the culture was adjusted to 8.5. Further analysis suggested volatile ammonia or amino acids maybe a cue for bacterial biofilm growth. The proteomics data suggested that V. cholerae was in a nutrient rich environment when supplemented with protozoal filtrate. In addition, an amino acid ABC transporter, responsible for general amino acid transport was up-regulated. This data may indicate that small molecules, such as amino acids in the protozoal supernatant may act as a trigger for biofilm formation by V. cholerae. These findings will serve as a stepping-stone for further detailed understanding of the interactions between V. cholerae and protozoa, which in turn will lead to a better understanding of how pathogenic bacteria evolve in the environment.